60=12+6(n-1)

Simple and best practice solution for 60=12+6(n-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 60=12+6(n-1) equation:


Simplifying
60 = 12 + 6(n + -1)

Reorder the terms:
60 = 12 + 6(-1 + n)
60 = 12 + (-1 * 6 + n * 6)
60 = 12 + (-6 + 6n)

Combine like terms: 12 + -6 = 6
60 = 6 + 6n

Solving
60 = 6 + 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
60 + -6n = 6 + 6n + -6n

Combine like terms: 6n + -6n = 0
60 + -6n = 6 + 0
60 + -6n = 6

Add '-60' to each side of the equation.
60 + -60 + -6n = 6 + -60

Combine like terms: 60 + -60 = 0
0 + -6n = 6 + -60
-6n = 6 + -60

Combine like terms: 6 + -60 = -54
-6n = -54

Divide each side by '-6'.
n = 9

Simplifying
n = 9

See similar equations:

| 2x(x-4)=-14x+8 | | 6x+27+3x+54=180 | | -17-5p=5(2+4p)+2p | | -58.75-x/8=7x/8+191.25 | | 14b-13b+3b=20 | | u(6u-7)=0 | | 4ln(7x)=16 | | -17-5p=5(2+4)+2p | | 3x^3-2x^2-12x+18=0 | | 6w+5w-9w=12 | | 5y(y+2)=0 | | 2tanx+7=3 | | 6+2x-5=6-3(2x-1) | | 10h-8h+h-3h+h=7 | | 5+3(x+4)=-(2x-1)-9 | | log[4](13*7)= | | 5r^2-10r-15=0 | | 2x^3+13x=8x^2 | | -17-55p=5(2+4p)+2p | | 20-2=38 | | -3(x-4)+2xy=xy-5x+xy-6 | | 2w^2-22w+48=0 | | 5(2)-2=38 | | (3g+2)(9g+5)=0 | | 5(10)-2=38 | | 300+12=960 | | 6-(x+9)=3-4x | | 10x-7y=-42 | | (d-6)(d-2)=0 | | 3(8)+7=25 | | 8(x+1)+3=7x+18 | | 3x-5(x+2)=12x+4 |

Equations solver categories